Partner Innovation Collaboration and Management Support Toward Innovation Speed and New Product Performance in Small Manufacturing Firms - Fansuri Munawar; Didi Tarmidi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
The purpose of this study was to examine and analyze the role of partner innovation collaboration and management support on innovation speed, and its implications towards new product performance in small manufacturing firms. This study took samples in the category of small manufacturing firms in the food & beverage sector, shoes & bags sector, craft sector, and diverse sector. Then, this study uses primary data using a questionnaire distributed to 95 owners or managers of small manufacturing firms in the Bandung and surrounding areas. Data analysis uses structural equation modeling based on partial least square with the help of SmartPLS 3.0. The results showed that partner innovation collaboration had a positive and significant effect on innovation speed, then management support had a positive and significant effect on innovation speed, then innovation speed had a positive and significant effect on new product performance, most recently the role of partner innovation collaboration also had a positive effect and significant to new product performance. The R-Square calculation results show that partner innovation collaboration and management support influence 0.432 on innovation speed, then partner innovation collaboration and innovation speed have an effect of 0.637 on new product performance. This study implied that small manufacturing firms to utilize an innovation collaboration with partners and allocate more time, effort, thought, costs in the effort to innovation, and be able to create an atmosphere of work together with employees that support innovation activities. Further research is to include moderation variables that support the improvement of new product performance such as absorptive capacity and technological uncertainty. Keywords: management support, partner innovation collaboration, innovation speed, new product performance